Maternal Nutrition Status and Its Relation with Low Birth Weight: A Meta Analysis Study - Titik Wijayanti; Atik Setyaningsih; Wahyuningsih Wahyuningsih (Journal of Epidemiology and Public Health, 2021)
Background: The condition of low birth weight (LBW) increases the risk of death in newborns early in life and results in health and development problems later in life. However, research related to factors associated with low birth weight is still limited. This study aimed to determine the risk factors associated with the nutritional status of mothers with low birth weight babies.Subjects and Method: This was a systematic review and meta-analysis by searching for articles published by the online database PubMed in 2016 to 2021. With P: Pregnant women, I: height <150 cm, maternal mid-upper arm circumference (MUAC) <23 cm, did not receive nutrition counseling, C: height > 150 cm, maternal MUAC >23 cm, receiving nutritional counseling, O: LBW. And the inclusion criteria of this study are: 1) articles that explain the influence of maternal nutritional status with LBW; 2) original research papers; 3) the research subjects were pregnant women who gave birth to LBW; 4) research using multivariate logistic regression analysis method. The dependent variable is low birth weight. The independent variable is a risk factor related to the nutritional status of the mother as measured by height, arm circumference, and the provision of nutritional counseling. Data analysis using RevMan software.Results: There are 18 articles on quantitative analysis. Pregnant women who have a height <150 cm (OR= 3.13; 95% CI= 0.75 to 13.10; p= 0.120) and maternal MUAC <23 cm (OR= 3.79; 95% CI= 3.00 to 4.78; p= 0.001) had a greater risk of giving birth to a baby with low birth weight. Likewise, pregnant women who did not receive nutritional counseling had a greater risk of experiencing low birth weight (OR= 2.98; 95% CI = 2.11 to 4.22; p= 0.001).Conclusion: Pregnant women who have a height <150 cm, MUAC <23 cm, and do not receive nutritional counseling have a greater risk of giving birth to babies with low birth weight.Keywords: low birth weight, nutritional status, maternal, neonatal.Correspondence: